Semantic Study on the Unique Naming of PTKIN Library and Information Journals - Ahwan, Muh Ahlis; Kardi, Kardi (PAROLE: Journal of Linguistics and Education, 2021)
The development of library and information science journals within Indonesian State Islamic Higher Education Institutions (PTKIN) has largely been discussed from managerial and bibliometric perspectives, while their linguistic aspects have received limited attention. This study examines the naming of PTKIN library and information journals from a semantic perspective, viewing journal names as meaningful linguistic constructions rather than purely administrative labels. Using a qualitative descriptive approach, journal names are analyzed as lexical data to identify their language sources, semantic structures, and symbolic functions. The findings indicate that PTKIN journal names consistently refer to concepts related to books, libraries, knowledge, and literacy, employing diverse linguistic resources such as Arabic, Indonesian, foreign languages, and local languages. These names operate across denotative, connotative, and symbolic levels of meaning, serving not only to mark disciplinary scope but also to express institutional identity and epistemic orientation. The study highlights journal naming as a structured linguistic practice shaped by disciplinary traditions and cultural contexts, and demonstrates the relevance of semantic and onomastic analysis for understanding academic publishing beyond managerial concerns.